From anthropocentric to biocentric: Reforming sociology education through hidden curriculum to prepare sustainability-oriented teachers in maluku - Afdhal; Feky Manuputty; Nathalia Debby Makaruku (12 Waiheru, 2025)
The reform of sociology education in the context of sustainability demands a paradigm shift from anthropocentric to biocentric thinking, particularly in preparing future teachers to internalise sustainability values rooted in local wisdom. This study aims to identify and analyse the role of the hidden curriculum in embedding sustainability values in prospective teachers in Maluku, within the context of sociology education. Using a qualitative case study approach, data were collected through participatory observation, in-depth interviews, document analysis, and focus group discussions (FGDs) involving the Department of Sociology at Universitas Pattimura and selected secondary schools in the Maluku region. The findings reveal that sustainability values are implicitly instilled through local cultural practices, such as Pela Gandong (social solidarity), Sasi Laut (customary marine conservation), and gotong royong (social and economic sustainability). Additionally, local historical narratives and myths contribute to students' ecological awareness. The study highlights the strategic potential of sociology education in shaping a sustainability-oriented mindset among future educators. Its novelty lies in identifying a contextual and applicable model of hidden curriculum based on local wisdom. The main recommendation is to design a more explicit curriculum that integrates sustainability values into both conceptual and practical dimensions of teaching and learning.